1990
DOI: 10.1111/j.1432-1033.1990.tb15522.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide activates immediate binding of a Drosophila factor to DNA heat‐shock regulatory element in vivo and in vitro

Abstract: The synthesis of heat-shock proteins via activation of heat-shock genes occurs in response to heat and various physical or chemical stressing agents. Transcriptional activation of heat-shock genes requires a heat-shock regulatory element in their promoter, to which a heat-shock specific transcription factor binds. In Drosophilu cells, the heat-shock factor already exists in unstressed cells in an inactive form and acquires the capacity to bind to the heat-shock element following stress. The mechanism of this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 47 publications
(35 reference statements)
2
11
0
Order By: Relevance
“…Through RNAi-dependent knockdown, we found that the protective function of ataxin-3 is reduced or eliminated by the knockdown of DnaJ-1 (which aligns with human DNAJB1, B4 and B5, at values < e−100 and with > 99% coverage, based on BLASTp results), by the knockdown of CG5001 (which also aligns with human DNAJB1, B4 and B5, at values < e−100 and with > 99% coverage, based on BLASTp results), and by the knockdown of Hsf (heat shock factor, which activates the transcription of inducible heat shock proteins during stress (Becker et al, 1990; Clos et al, 1990; Westwood et al, 1991)) (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…Through RNAi-dependent knockdown, we found that the protective function of ataxin-3 is reduced or eliminated by the knockdown of DnaJ-1 (which aligns with human DNAJB1, B4 and B5, at values < e−100 and with > 99% coverage, based on BLASTp results), by the knockdown of CG5001 (which also aligns with human DNAJB1, B4 and B5, at values < e−100 and with > 99% coverage, based on BLASTp results), and by the knockdown of Hsf (heat shock factor, which activates the transcription of inducible heat shock proteins during stress (Becker et al, 1990; Clos et al, 1990; Westwood et al, 1991)) (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…A secondary assumption would be that these induced changes in gene expression would then have profound effects in later stages of the life cycle. The existence of such chemicals has been demonstrated in several organisms, including Drosophila (Botella et al, 1985;Becker et a!., 1990;Crowl & Covich, 1990;Pritsos et al, 1990;Storz et al, 1990). We know that the chemical composition of the HD food appears to be somewhat different in its pH and reducing ability from that of the LD food (data not shown).…”
Section: Larval Development and Adult Longevitymentioning
confidence: 90%
“…there are many similarities between the signal transduc-Hypotheses conceming the central role of thiol disultion pathways in the different systems, for example, H2O2 phide exchange reactions in stress tolerance have existed induces HSPs and/or thermotolerance in foc/zenc/zw co// for many years (Levitt 1962). It is clear, for example, (Privalle and Fridovich 1987), Synechococcus R2 (Mit-that desiccated tissues accumulate GSSG and that protier and Tel-Or 1991), Drosophila, animal and human tein-glutathione mixed disulphides increase in plants cells (Becker et al 1990, Cornelius 1996, Kerendian et subjected to drought (Kranner and Grill 1996. Associaal.…”
Section: ) and Is Accompanied By An Inhibitory Effectmentioning
confidence: 99%